INFORMATION SYSTEM FOR FORECASTING NONLINEAR NON-STATIONARY PROCESSES IN FINANCE - Петро Бідюк; Роман Тертичний; Денис Чупрін (KPI Science News)
Background. Financial processes are often characterised by nonlinearity and non-stationarity, which makes them difficult to accurately model and forecast. Traditional methods cannot effectively take into account the complex interrelationships and variability of such processes, which generates increased uncertainty and risks. This leads to the need to develop new information systems and methods to improve the accuracy and sustainability of forecasts.